Multilayer electrode, method for producing an electrode and electrochemical energy storage device
By using silicon-carbon composite materials with different particle sizes in the electrodes of electrochemical energy storage devices, the problems of capacity loss and long charging time of lithium-ion batteries during cycling are solved, fast charging and high cycle stability are achieved, and reduced manufacturing costs.
Patent Information
- Application Number
- CN202380044226.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-14
- Filing Date
- 2023-04-14
- Publication Date
- 2025-01-21
AI Technical Summary
Existing lithium-ion batteries are prone to capacity loss during the charging and discharging cycles, and the charging time is long, which affects the electric driving distance.
Using an electrode including at least one current collector, a first silicon carbon composite material and a second silicon carbon composite material, the first silicon carbon composite material contains larger first particles, and the second silicon carbon composite material contains smaller second particles , by adjusting the particle size and distribution, the charging capacity and cycle stability of the electrode are improved.
Improved fast charging capabilities and cycle stability of electrochemical energy storage devices, reduced lithium ion dynamics, increased overall capacity potential of electrodes, and reduced manufacturing costs.
Smart Images

Figure CN119343781A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to an electrode for an electrochemical energy storage device, the electrode comprising at least one current collector, a first silicon-carbon composite material (which comprises a plurality of first particles) and a second silicon-carbon composite material (which comprises a plurality of second particles). In addition, the present disclosure relates to an electrochemical energy storage device and a method for manufacturing an electrode. Background Art
[0002] Lithium-ion batteries are widely used and provide stored energy for different components. Especially in electric and hybrid vehicles, lithium-ion batteries provide electrical energy for vehicle components and the powertrain. In such applications, it is highly desirable to achieve a longer electric driving range, which can be achieved by increasing the capacity of the battery. One disadvantage of increasing the battery capacity is that the charging time also increases.
[0003] Furthermore, it is well known that lithium-ion batteries degrade over a period of time. In particular, the electrochemical cells of the battery are susceptible to capacity loss as the number of charge and discharge cycles increases, in which a solid electrolyte interphase (SEI layer) is formed on the negative electrode based on various mechanisms, which competes with the reversible lithium insertion. The SEI layer is usually formed during the charge and discharge cycles of the electrochemical cell due to the reduction of organic solvents and anions on the electrode surface. In this case, most of the formation occurs during the first charge and discharge cycle of the electrochemical cell. In the prior art, it is well known that the SEI layer plays an important role in the safety, performance and cycle life of the electrochemical cells in lithium-ion batteries.
[0004] WO2020 / 177624A1 discloses an electrode arrangement having a negative electrode film, the negative electrode film comprising a first coating and a second coating. The first coating is the outermost layer of the negative electrode film, and the first coating comprises a first negative electrode active material. The second coating is disposed between the first coating and the negative electrode current collector, and the second coating comprises a second negative electrode active material. Both the first negative electrode active material and the second negative electrode active material comprise a silicon-based material and a carbon material, but the mass percentage of the silicon-based material is different. Summary of the invention
[0005] The object of the present disclosure is to provide an electrode and an electrochemical energy storage device with improved charging capability. Another object of the present disclosure is to provide a method for low-cost production of electrodes for electrochemical energy storage devices. This object is achieved by the subject matter of the independent claim. Further improvements of the subject matter of the independent claim are provided in the dependent claims.
[0006] According to one aspect of the present disclosure, an electrode for an electrochemical energy storage device is disclosed. In a preferred embodiment, the electrode can be formed as an anode of the electrochemical energy storage device.
[0007] The electrode comprises at least one current collector, a first silicon-carbon composite material and a second silicon-carbon composite material. The first silicon-carbon composite material comprises a plurality of first particles. The second silicon-carbon composite material comprises a plurality of second particles. The first silicon-carbon composite material and the second silicon-carbon composite material are connected to the current collector.
[0008] The plurality of first particles may be formed into a porous carbon scaffold having micropores and mesopores, wherein silicon is incorporated into the micropores and mesopores of the carbon scaffold; the plurality of second particles may be formed into a porous carbon scaffold having micropores and mesopores, wherein silicon is incorporated into the micropores and mesopores of the carbon scaffold.
[0009] Additionally or alternatively, the plurality of first particles may be formed as graphite having a surface wherein silicon is deposited as Si particles or Si wires on the surface of the graphite, and the plurality of second particles may be formed as graphite having a surface wherein silicon is deposited as Si particles or Si wires on the surface of the graphite.
[0010] Preferably, the first silicon-carbon composite material is formed as a first coating layer of the current collector, and the second silicon-carbon composite material is formed as a second coating layer of the current collector.
[0011] According to one embodiment of the present invention, the particle size of the first particles is larger than the particle size of the second particles. By providing larger first particles in the first layer and smaller particles in the second layer, the reactive surface in the second layer is higher than that in the first layer. Therefore, the second layer in direct contact with the electrolyte can bind a larger amount of lithium ions in a shorter time. Therefore, the fast charging capability of the electrochemical energy storage device including the electrode of the present invention is improved (especially due to faster kinetics in the second layer). The faster kinetics of ions in the second layer is due to higher surface area and higher tortuosity (e.g., more pores).
[0012] Typically, silicon in a porous carbon support having micropores and mesopores or silicon on the surface of graphite particles is introduced into the pores of the porous carbon support or on the surface of graphite particles by chemical vapor infiltration (CVI) reaction of a silicon-containing gas (e.g., monosilane, such as silicon hydride (SiH4)). A description of such a process is described in U.S. Publication No. 2017 / 0170477, the entire contents of which are hereby incorporated by reference in their entirety for reference.
[0013] The present disclosure also provides another advantage, that is, the distribution of the first silicon-carbon composite material allows for a higher packing density and improves the conductivity between the second layer and the current collector. In addition, the first layer allows for increased capacity, while the kinetics within the first layer are slower.
[0014] According to an alternative embodiment, the particle size of the second particles is larger than the particle size of the first particles. By providing a second layer with larger particles, the kinetics of lithium ions can be reduced due to the smaller surface area of the second particles within the second layer. The reduction in lithium ion kinetics results in less thermal stress in an electrochemical energy storage device or suitable electrochemical battery cell having an electrode of the present disclosure. Therefore, by providing a second layer with larger second particles than the first particles, the cycling stability and durability of the electrochemical energy storage device can be improved.
[0015] According to one embodiment of the present invention, a plurality of first particles are formed into a porous carbon scaffold having micropores and mesopores, wherein silicon is incorporated into the micropores and mesopores of the carbon scaffold. The carbon scaffold is formed in a first layer comprising micropores and mesopores. Additionally or alternatively, the carbon scaffold may comprise macropores. Thus, the energy density within the first layer may be increased.
[0016] In addition, the plurality of second particles are formed into a porous carbon scaffold having micropores and mesopores, wherein silicon is incorporated into the micropores and mesopores of the carbon scaffold. The carbon scaffold is formed in a second layer comprising micropores and mesopores. Additionally or alternatively, the carbon scaffold may comprise macropores. Thus, the energy density within the second layer may be increased.
[0017] According to another embodiment, which may be present in addition to or as an alternative to the first embodiment, the plurality of first particles is formed as graphite having a surface, wherein silicon is deposited as Si particles or Si wires on the surface of the graphite.
[0018] Accordingly, the plurality of second particles may be formed as graphite having a surface, wherein silicon is deposited as Si particles or Si wires on the surface of the graphite.
[0019] According to one embodiment of the electrode, the second silicon-carbon composite material is interconnected with the current collector via the first silicon-carbon composite material. Thus, by providing the first silicon-carbon composite, the thickness of the second silicon-carbon composite can be reduced without sacrificing the overall capacity potential of the electrode. In particular, the first silicon-carbon composite can be formed as a low-cost material, and the second silicon-carbon composite can be formed as an advanced and more expensive material. Thus, by utilizing the first layer, the amount of expensive material can be reduced, and thus the electrode can be manufactured more cost-effectively and efficiently.
[0020] If the plurality of first particles of the first silicon-carbon composite material have a Dv50 particle size distribution of >8 μm, the surface area of the first particles (especially the BET surface area, also referred to as the BET specific surface area, which can be measured by the BET method) can be reduced compared to the second particles. Correspondingly, if the plurality of second particles of the second silicon-carbon composite material have a Dv50 particle size distribution of <6 μm, the surface area of the second particles (especially the BET surface area) can be increased. Therefore, based on the Brunauer-Emmett-Teller (BET) theory, the specific surface area of the first layer and the second layer for the physical adsorption of lithium ions is adjusted to maximize the rapid charging of the resulting electrode.
[0021] The overall particle distribution of each of the first layer and / or the second layer may be multimodal or unimodal. For example, the second layer may be formed of a multimodal material to increase density and tortuosity.
[0022] The particle size distribution can be measured according to methods known in the art. For example, the particle size distribution can be measured by laser scattering of particles in a suspension, powder time-of-flight method, or other methods known in the art. As known in the art, the particle size distribution can be expressed as a particle number distribution or a particle volume distribution. Therefore, the particle size distribution can be expressed as Dvx, where D represents the particle size, v represents the value corresponding to the volume basis, and x represents the cumulative percentage of the particles. For example, Dv1, Dv10, Dv50, Dv90, and Dv99 are the diameters when 1%, 10%, 50%, 90%, and 99% of a plurality of particles in a given volume distribution are below a specified micron size. The particle size distribution is bounded by D0 (the smallest particle in the distribution) and Dv100 (the largest size of the largest particle); Dv50 is the volume average particle size. The particle size distribution can be described by one or more modes present in the particle size distribution, where the concept of mode is known in the art, for example, a mode is a maximum value in the distribution. The particle size distribution can be unimodal or multimodal, for example, bimodal or trimodal. Modes in a multimodal particle size distribution may include distinct local maxima in the particle size distribution and / or shoulders that can be resolved by first and / or second derivatives of the particle size distribution.
[0023] According to one embodiment of the present disclosure, the particle size and / or particle size distribution can be obtained based on the measurement of an electron microscope (e.g., a scanning electron microscope (SEM) or a scanning tunneling microscope (STM)). After manufacturing an electrode having a first layer and a second layer, a cross section through the two layers of the electrode and the current collector can be measured to obtain the particle size, pore size, and particle size distribution. Therefore, the median particle size or the average particle size can be accurately measured in order to classify the electrode and / or check its quality.
[0024] According to another embodiment, the first silicon-carbon composite material has a first BET surface area, and the first BET surface area of the first silicon-carbon composite material is less than the second BET surface area of the second silicon-carbon composite material. Therefore, compared with the dynamics of lithium ions in the first layer, the dynamics of lithium ions in the second layer of the electrode are accelerated due to the increased BET surface area.
[0025] If the first silicon-carbon composite material has a Si / C content between greater than 0 wt % and 70 wt % (including 70 wt %) relative to the first silicon-carbon composite material, the particle size distribution and density of the first layer material and the second layer material can be further controlled. In another embodiment, the second silicon-carbon composite material has a Si / C content between 50 wt % and 100 wt % (including 50 wt % to 100 wt %) relative to the second silicon-carbon composite material. Therefore, the Si / C content of the appropriate layer material provides additional adjustment possibilities.
[0026] When the plurality of first particles are formed into graphite having a surface, wherein silicon is deposited on the surface of the graphite as Si particles or Si wires, the first silicon-carbon composite material comprises the plurality of first particles, and the first silicon-carbon composite material has a Si / C content between greater than 0 wt % and 30 wt % (including 30 wt %) relative to the first silicon-carbon composite material.
[0027] Accordingly, when the plurality of second particles are formed into graphite having a surface, wherein silicon is deposited on the surface of the graphite as Si particles or Si wires, the second silicon-carbon composite material comprises the plurality of second particles, and the second silicon-carbon composite material has a Si / C content between greater than 0 wt % and 30 wt % (including 30 wt %) relative to the second silicon-carbon composite material.
[0028] According to another embodiment, the first layer further comprises graphite particles and / or carbon black particles and / or carbon nanotubes in addition to the first silicon-carbon composite material. When other graphite particles are present, these graphite particles do not contain silicon as described above for the first particles and / or the second particles. In addition, the second layer further comprises graphite particles and / or carbon black particles in addition to the second silicon-carbon composite material. For example, the volume content of graphite particles and / or carbon black particles can be set to 30%. The average size of suitable graphite particles can be several microns. The average size of carbon black particles can be 30-100nm. In particular, carbon black particles can increase the conductivity within the electrode layer. By inserting carbon nanotubes, the electrical connection between the first layer and the current collector can be improved. This results in a reduction in the resistance of the electrode in the transition region between the first layer and the current collector.
[0029] If the current collector is formed as a metal foil or a metal alloy foil, it can be easily formed technically. Preferably, the current collector may be formed of copper, or may contain copper, such as a copper alloy.
[0030] According to another aspect of the present invention, a method for manufacturing an electrode is provided. In a first step, a first silicon-carbon composite mixture combined with a binder solution is provided, the first silicon-carbon composite mixture containing graphite particles and / or carbon black particles and / or carbon nanotubes. In addition, a second silicon-carbon composite mixture combined with a binder solution is provided, the second silicon-carbon composite mixture containing graphite particles and / or carbon black particles. Then, the first silicon-carbon composite mixture combined with the binder solution is applied as a first layer to at least one current collector formed as a conductive foil. In another step, the second silicon-carbon composite mixture combined with the binder solution is applied as a second layer onto the first layer. After drying at a temperature of 100°C to 140°C, an electrode is formed.
[0031] The first silicon-carbon composite mixture or the second silicon-carbon composite mixture refers to a mixture in which the first silicon-carbon composite material or the second silicon-carbon composite material exists.
[0032] Therefore, the first layer is applied to the current collector as a mixture paste, and the second layer is also applied to the first layer as a mixture paste. Based on a preferred embodiment, the first silicon-carbon composite mixture combined with the binder solution and / or the second silicon-carbon composite mixture combined with the binder solution are applied to the current collector by curtain coating. Additional graphite particles and / or carbon black particles and / or carbon nanotubes can also be mixed into the mixture and applied by curtain coating. By curtain coating the current collector, a constant layer thickness can be maintained. In addition, the manufacturing cost of the electrode and the electrochemical energy storage device can be reduced.
[0033] The electrode may be formed as an anode electrode, which is used as a positive electrode in an electrochemical energy storage device. According to another aspect of the present invention, an electrochemical energy storage device is provided, which may be formed as a lithium-ion battery. As required, the electrochemical energy storage device may be formed as a battery cell, a battery pack, a battery module or a battery system.
[0034] The electrochemical energy storage device comprises at least one electrode, which is formed as a cathode electrode. In addition, the electrochemical energy storage device comprises at least one electrode of the present invention (which is formed as an anode electrode), and at least one separator disposed between the anode electrode and the cathode electrode. The electrolyte provides a supply of lithium ions between the electrodes. In addition, another separator may be disposed between the electrodes to prevent the electrodes from short-circuiting.
[0035] According to one embodiment of the present invention, a first silicon-carbon composite mixture is disclosed. The first silicon-carbon composite mixture comprises a first silicon-carbon composite material having a porous carbon support, wherein the porous carbon support comprises micropores and mesopores and has a total pore volume of not less than 0.5 cm 3 Preferably, the first silicon-carbon composite material has a silicon content of 30% to 70% and has a plurality of particles, and the Dv50 of the particles is 6 μm to 20 μm.
[0036] Another embodiment of the present invention provides a second silicon-carbon composite mixture having at least one second silicon-carbon composite material. The at least one second silicon-carbon composite material comprises at least one other carbon support having micropores and mesopores and a total pore volume of not less than 0.5 cm 3 Preferably, the second silicon-carbon composite material has a silicon content of 30% to 70% and has a plurality of particles, and the Dv50 of the particles is 1 μm to 6 μm.
[0037] Binder is a binding agent or bonding material. Therefore, a binder refers to a material that can bind the various components (particularly particles) of a substance (e.g., carbon) together. The binder is generally arranged so that when the particles are combined with the corresponding binder, a cohesive substance is formed, which can be further formed into a new form. In another embodiment, the silicon-carbon composite mixture includes at least one other binder. The advantage brought by this is that carbon improves the conductivity of the electrode, thereby providing better electrical conductivity. At least one other binder further supports mechanical stability. Another carbon can be a hard carbon material or graphite carbon or a metal oxide.
[0038] According to another aspect of the present invention, an alternative method for manufacturing an electrode is provided. In a first step, a first dried silicon-carbon composite mixture combined with a binder powder is provided, the first dried silicon-carbon composite mixture comprising graphite particles and / or carbon black particles. In another step, a second dried silicon-carbon composite mixture combined with a binder powder is provided, the second dried silicon-carbon composite mixture comprising graphite particles and / or carbon black particles. The first silicon-carbon composite mixture combined with the binder powder is applied as a first layer to at least one current collector formed as a conductive foil by a calendering method, and the second silicon-carbon composite mixture combined with the binder powder is applied as a second layer to the first layer by a calendering method.
[0039] Therefore, alternative manufacturing methods enable a dry or semi-dry manufacturing process, followed by a compaction step through one or more calendering rollers to press the powder mixture onto the current collector. By using calendering rollers, a constant layer height and a constant particle size distribution can be ensured. The mixture and the current collector can be pressed through one or more subsequent calendering rollers or calendering roller assemblies.
[0040] Depending on the manufacturing process, a subsequent drying step may be required. According to one embodiment, the drying process is performed after applying the first layer and the second layer. Alternatively, a first drying process is performed after applying the first layer, and a second drying process is performed after applying the second layer. By performing the drying process after applying the first layer and the second layer, an accelerated manufacturing process can be provided. Multi-step drying processes allow for more consistent and controlled manufacturing conditions.
[0041] It is noted that if a percentage is given without further definition, the percentage refers to weight %.
[0042] The present disclosure will be described in more detail below based on the exemplary embodiments shown in the accompanying drawings: BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 shows a cross-sectional view of an electrode according to one embodiment of the present invention,
[0044] Figure 2 shows Figure 1 A flow chart of a method for manufacturing an electrode is shown, and
[0045] Figure 3 shows cross sections of different electrodes. DETAILED DESCRIPTION
[0046] In the drawings, the same reference numerals represent similar elements. The sizes and relative positions of the elements in the drawings are not necessarily drawn to scale, and some elements are enlarged and placed to improve the readability of the drawings. In addition, the specific shapes of the drawn elements are not intended to convey any information about the actual shape of the specific elements, but are only selected for ease of identification in the drawings.
[0047] Unless the context requires otherwise, in this specification and claims, the term "comprise" and variations thereof, such as "include" and "contain" should be interpreted in an open, inclusive sense, i.e., "including but not limited to". Unless otherwise stated, in this specification, any concentration range, percentage range, ratio range or integer range should be understood to include any integer value within the range, and, where appropriate, fractions thereof (such as one tenth and one hundredth of an integer). Unless otherwise stated, the terms "about" and "approximately" as used herein mean ±20%, ±10%, ±5% or ±1% of the range, value or structure. It should be understood that the terms "a" and "an" as used herein refer to "one or more" of the listed components. The use of alternatives (such as "or") should be understood to mean one, two or any combination of the alternatives.
[0048] References in this specification to "one embodiment" or "an embodiment" mean that a particular feature, structure, or characteristic described in connection with that embodiment is included in at least one embodiment of the present disclosure. Therefore, the phrases "in one embodiment" or "in an embodiment" appearing in various places in this specification do not necessarily all refer to the same embodiment. Furthermore, in one or more embodiments, the particular features, structures, or characteristics may be combined in any suitable manner.
[0049] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present disclosure belongs. As used in the specification and claims, the singular forms "a", "an", and "the" include plural references unless the context clearly dictates otherwise.
[0050] Figure 1 A cross-sectional view of an electrode 1 according to one embodiment of the present invention is shown. The electrode 1 is formed as a cathode electrode of an electrochemical energy storage device (eg, a lithium-ion battery cell) not shown. The electrode 1 comprises at least one current collector 2, a first coating 4, and a second coating 6.
[0051] In the illustrated example, the current collector 2 is formed as a copper foil. The current collector 2 may be formed as a continuous foil sheet or may be formed as a foil segment having a predetermined length and width.
[0052] The first coating layer 4 is formed of a first silicon-carbon composite material, and the second coating layer 6 is formed of a second silicon-carbon composite material.
[0053] The plurality of first particles form a porous carbon scaffold having micropores and mesopores. In particular, silicon is incorporated into the micropores and mesopores of the carbon scaffold. Accordingly, the plurality of second particles form a porous carbon scaffold having micropores and mesopores, wherein silicon is incorporated into the micropores and mesopores of the carbon scaffold of the second particles.
[0054] The first silicon-carbon composite material and the second silicon-carbon composite material are connected to the current collector 2 , the first coating 4 is applied directly on the current collector 2 or indirectly on the current collector 2 with the aid of a primer, and the second coating 6 is disposed on the first coating 4 .
[0055] According to the illustrated embodiment, the particle size of the first particles is larger than that of the second particles. For example, the average particle size of the second particles in the second layer 6 may be less than 6 μm, while the average particle size of the first particles in the first layer 4 may be greater than 8 μm.
[0056] The term "carbon part" in silicon-carbon composites refers to a material or substance consisting of or at least containing carbon. In this regard, carbon materials can include high purity, amorphous and crystalline materials. The carbon material can be activated carbon, pyrolyzed dry polymer gel, pyrolyzed polymer cryogel, pyrolyzed polymer xerogel, pyrolyzed polymer aerogel, activated dry polymer gel, activated polymer cryogel, activated polymer xerogel, activated polymer aerogel or a combination thereof. In another embodiment, carbon can be produced by pyrolysis of coconut shells or other organic wastes. In this regard, polymers are molecules containing more than two repeating structural units. Porous carbon (also referred to as porous carbon materials) has the advantages of being generally easy to produce, generally low in impurity content and large in pore volume. Therefore, porous carbon exhibits good electrical conductivity and high mechanical and chemical stability. In one embodiment, the carbon material has a high micropore volume ratio. Typically, porous carbon has a pore space, also referred to as a pore volume, wherein the pore space is a group of voids (pores) in carbon that can be filled with gas or fluid. In this regard, the properties and methods of making porous carbon are described in the prior art, such as U.S. Publication No. 2017 / 0015559, the entire disclosure of which is hereby incorporated by reference in its entirety for all purposes.
[0057] The Si portion of the silicon-carbon composite material may be pure silicon or a material composition containing silicon. For example, the Si portion may be at least one alloy. The alloy may be a silicon-titanium alloy (Si-Ti), a silicon-iron alloy (Si-Fe), or a silicon-nickel alloy (Si-Ni). In another embodiment, the Si portion may be composed of a P dopant, an As dopant, or an N dopant. The P dopant is typically a phosphorus dopant, the As dopant is typically an arsenic dopant, and the N dopant is typically a nitrogen dopant.
[0058] The surface area of the silicon-carbon composite is determined, for example, by thermogravimetric analysis to determine its silicon content. The silicon-carbon composite can also be tested in a half-cell coin cell. The anode of the half-cell coin cell can contain 60-90% silicon-carbon composite, 5-20% Na-CMC (as a binder) and 5-20% Super C45 (as a conductivity enhancer), and the electrolyte can contain, for example, 2:1 ethylene carbonate: diethylene carbonate, 1M LiPF6 and 10% fluoroethylene carbonate. The half-cell coin cell can be cycled at a rate of C / 5 for 5 cycles at 25°C and then at a rate of C / 10. The voltage can be cycled between 0V and 0.8V, or the voltage can be cycled between 0V and 1.5V. From the half-cell coin cell data, the maximum capacity can be measured, as well as the average coulombic efficiency (CE) in the range of the 7th cycle to the 20th cycle.
[0059] Figure 2a and Figure 2b Shown to illustrate the manufacturing Figure 1 Flowcharts of two exemplary methods of electrode 1 shown in FIG. In particular, Figure 2a A method 10 according to a first embodiment is shown, which applies the first layer 4 and the second layer 6 to the current collector 2 by means of curtain coating.
[0060] In a first step 11 , a first silicon-carbon composite mixture combined with a binder solution is provided, the first silicon-carbon composite mixture comprising graphite particles and / or carbon black particles and / or carbon nanotubes.
[0061] Furthermore, as a second step or a step 12 in parallel with the first step 11 , a second silicon-carbon composite mixture combined with a binder solution is provided, the second silicon-carbon composite mixture comprising graphite particles and / or carbon black particles.
[0062] Therefore, the first silicon-carbon composite mixture and the second silicon-carbon composite mixture are both provided in the form of a mixture paste, and the mixture paste can be applied to the current collector 2 by a curtain coating method.
[0063] As a binder, styrene-butadiene gum / carboxymethyl cellulose (CMC / SBR) blends, polyacrylic acid (PAA) and / or lithium polyacrylate (LiPAA) or sodium polyacrylate (NaPAA) can be used. In alternative embodiments, the binder is formed as a fluoropolymer, such as polytetrafluoroethylene (PTFE), perfluoroalkoxy polymer resin (PFA), fluorinated ethylene propylene (FEP), polyethylene tetrafluoroethylene (ETFE), polyvinyl fluoride (PVF), polyethylene trifluorochloroethylene (ECTFE), polyvinylidene fluoride (PCDF), polytrifluorochloroethylene (PCTFE), trifluoroethanol, or a combination of at least one of these materials and at least one other material. In another embodiment, the binder is a copolymer of polyimide or polyacrylic acid and styrene-butadiene.
[0064] Then, in step 13 , the first silicon-carbon composite mixture combined with the binder solution is applied as a first layer 4 onto at least one current collector 2 formed as a conductive foil.
[0065] In a further step 14 , a second silicon-carbon composite mixture in combination with a binder solution is applied as a second layer 6 onto the first layer 4 .
[0066] Finally, a drying process is performed at a temperature of 100° C. to 140° C. to form the electrode 1 .
[0067] Figure 2b A method 20 according to a second embodiment is shown, which applies the first layer 4 and the second layer 6 to the current collector 2 by means of a calendering method. The method 20 according to the second embodiment is also used to form an electrode 1 .
[0068] In a first step 21, a first dry silicon-carbon composite mixture is provided, the first dry silicon-carbon composite mixture comprising graphite particles and / or carbon black particles combined with a binder powder. Compared to the method 10 according to the first embodiment, the binder is used in powder form instead of in solution form.
[0069] In another step 22, a second dried silicon-carbon composite mixture is provided in combination with a binder powder, the second dried silicon-carbon composite mixture comprising graphite particles and / or carbon black particles.
[0070] Next, in step 23, the first silicon-carbon composite mixture combined with the binder powder is applied as a first layer 4 to at least one current collector 2 formed as a conductive foil by calendaring. In another step 24, the second silicon-carbon composite mixture combined with the binder powder is applied as a second layer 6 on top of the first layer 4 by calendaring.
[0071] The method 20 enables a dry or semi-dry manufacturing process with a subsequent compaction step by one or more calendering rollers to press the powder mixture onto the current collector 2 .
[0072] exist Figure 3a , Figure 3b and Figure 3c . In addition, the cross-sections are exemplary and are used to visualize the individual first and second particles within the layers. For illustration purposes, the individual layers are highlighted. In particular, Figure 3a A comparative example of an electrode 100 is shown in which a multimodal silicon-carbon material 104 is applied to a current collector 102. The silicon-carbon material 104 may include particles of different average sizes that are mixed to achieve a denser particle package.
[0073] Figure 3c Shown according to Figure 1 Cross section of the electrode 1 of the embodiment shown. Thus, the average size of the second particles in the second layer 6 or the second coating 6 is smaller than the average size of the first particles provided in the first layer 4 or the first coating 4. The second layer 6, which is first exposed to the electrolyte, has a higher surface area, which can accelerate the kinetics of lithium ions in the electrolyte. An energy storage device having the electrode 1 can charge the first part of its capacity in a shorter time.
[0074] Figure 3b Another embodiment of the electrode 1 is shown. Figure 3c or Figure 1Unlike the embodiment shown, the average size of the first particles in the first layer 4 is smaller than the second particles in the second layer 6. Therefore, the second particles in the second layer 6 form a barrier that reduces the kinetics of lithium ions. By reducing the kinetics of lithium ions during charging and discharging of a suitable electrochemical device, the long-term stability and durability of the electrochemical device can be improved due to less thermal stress.
Claims
1. An electrode (1) for an electrochemical energy storage device, comprising: - at least one current collector (2), - a first silicon-carbon composite material, comprising a plurality of first particles, - a second silicon-carbon composite material, comprising a plurality of second particles, The first silicon-carbon composite material and the second silicon-carbon composite material are connected to the current collector (2), characterized in that the first silicon-carbon composite material is formed as a first coating (4) of the current collector (2), and the second silicon-carbon composite material is formed as a second coating (6) of the current collector (2), wherein - the plurality of first particles are formed into a porous carbon scaffold having micropores and mesopores, wherein silicon is incorporated into the micropores and mesopores of the carbon scaffold; and wherein the plurality of second particles are formed into a porous carbon scaffold having micropores and mesopores, wherein silicon is incorporated into the micropores and mesopores of the carbon scaffold, or wherein - the plurality of first particles are formed as graphite having a surface, wherein silicon is deposited on the surface of the graphite as Si particles or Si wires, and wherein the plurality of second particles are formed as graphite having a surface, wherein silicon is deposited on the surface of the graphite as Si particles or Si wires. 2 . The electrode according to claim 1 , wherein a particle size of the first particles is larger than a particle size of the second particles. The electrode according to claim 1 , wherein a particle size of the second particles is larger than a particle size of the first particles. 4 . The electrode according to claim 1 , wherein the second silicon-carbon composite material is interconnected with the current collector through the first silicon-carbon composite material. 5 . The electrode according to claim 1 , wherein the plurality of first particles of the first silicon-carbon composite material have a particle size distribution Dv50 of >8 μm measured by a laser scattering method. 6 . The electrode according to claim 1 , wherein the plurality of second particles of the second silicon-carbon composite material have a particle size distribution Dv50 of <6 μm measured by a laser scattering method.
7. The electrode according to any one of claims 1 to 6, wherein the first silicon-carbon composite material has a first BET specific surface area, and the first BET specific surface area is smaller than a second BET specific surface area of the second silicon-carbon composite material.
8. An electrode according to any one of claims 1 to 7, wherein the first silicon-carbon composite material comprises a plurality of first particles, the plurality of first particles having a Si / C content between greater than 0 wt % and 70 wt %, including 70 wt %, relative to the silicon-carbon composite material, wherein the first particles are formed into a porous carbon scaffold having micropores and mesopores, wherein silicon is incorporated into the micropores and mesopores of the carbon scaffold.
9. An electrode according to any one of claims 1 to 8, wherein the second silicon-carbon composite material comprises a plurality of second particles, the plurality of second particles having a Si / C content between 50 wt % and 100 wt %, inclusive, relative to the silicon-carbon composite material, wherein the second particles are formed into a porous carbon scaffold having micropores and mesopores, wherein silicon is incorporated into the micropores and mesopores of the carbon scaffold.
10. An electrode according to any one of claims 1 to 9, wherein the first silicon-carbon composite material comprises a plurality of first particles, the plurality of first particles having a Si / C content between greater than 0 wt % and 30 wt %, including 30 wt %, relative to the silicon-carbon composite material, wherein the plurality of first particles are formed into graphite having a surface, wherein silicon is deposited on the surface of the graphite as Si particles or Si wires.
11. An electrode according to any one of claims 1 to 10, wherein the second silicon-carbon composite material comprises a plurality of second particles, the plurality of second particles having a Si / C content between greater than 0 wt% and 30 wt%, including 30 wt%, relative to the silicon-carbon composite material, wherein the plurality of second particles are formed into graphite having a surface, wherein silicon is deposited on the surface of the graphite as Si particles or Si wires.
12. An electrode according to any one of claims 1 to 11, wherein in addition to the first silicon-carbon composite material, the first layer (4) also contains graphite particles and / or carbon black particles and / or carbon nanotubes; wherein in addition to the second silicon-carbon composite material, the second layer (6) also contains graphite particles and / or carbon black particles.
13. The electrode according to any one of claims 1 to 12, wherein the current collector (2) is formed as a metal foil or a metal alloy foil, in particular, the current collector is formed of copper or contains copper.
14. Method (10) for producing an electrode (1) according to any one of claims 1 to 13, wherein - providing a first silicon-carbon composite mixture combined with a binder solution, wherein the first silicon-carbon composite mixture comprises graphite particles and / or carbon black particles and / or carbon nanotubes, - providing a second silicon-carbon composite mixture combined with a binder solution, and the second silicon-carbon composite mixture comprises graphite particles and / or carbon black particles, - applying said first silicon-carbon composite mixture in combination with a binder solution as a first layer (4) to at least one current collector (2), said at least one current collector (2) being formed as a conductive foil, - applying said second silicon-carbon composite mixture combined with a binder solution as a second layer (6) on top of said first layer (4), - After drying at a temperature of 100°C to 140°C, the electrode (1) is formed. 15 . The method of claim 14 , wherein the first silicon-carbon composite mixture combined with a binder solution and / or the second silicon-carbon composite mixture combined with a binder solution is applied to the current collector by a curtain coating method.
16. The method according to claim 14 or 15, wherein the drying process is performed after applying the first layer (4) and the second layer (6), or, A first drying process is performed after applying the first layer (4), and a second drying process is performed after applying the second layer (6).
17. The method according to any one of claims 14 to 16, wherein carbon nanotubes are provided in the first silicon-carbon composite mixture combined with the binder solution.
18. An electrochemical energy storage device, in particular formed as a lithium-ion battery, comprising at least one electrode (1) according to any one of claims 1 to 13, wherein the electrode (1) is formed as an anode electrode, the electrochemical energy storage device also comprising at least one cathode electrode and at least one separator arranged between the anode electrode and the cathode electrode, and comprising an electrolyte containing lithium ions.
19. A method (20) for producing an electrode (1) according to any one of claims 1 to 13, wherein - providing a first dry silicon-carbon composite mixture in combination with a binder powder, the first dry silicon-carbon composite mixture comprising graphite particles and / or carbon black particles, - providing a second dried silicon-carbon composite mixture in combination with a binder powder, the second dried silicon-carbon composite mixture comprising graphite particles and / or carbon black particles, - The first silicon-carbon composite mixture combined with a binder powder is applied as a first layer (4) by calendering to at least one current collector (2), the at least one current collector (2) being formed as a conductive foil, and the second silicon-carbon composite mixture combined with a binder powder is applied as a second layer (6) on top of the first layer (4) by calendering.
Citation Information
Patent Citations
Novel methods for sol-gel polymerization in absence of solvent and creation of tunable carbon structure from same
US20170015559A1
Novel materials with extremely durable intercalation of lithium and manufacturing methods thereof
US20170170477A1
Negative electrode plate, secondary battery and device having same
WO2020177624A1